Answer: x= -2
Explanation:
Given the equation
![4^(5x)=(16)^((2x-1))](https://img.qammunity.org/2020/formulas/mathematics/high-school/2yx8oabmxoioq9lz65v3zwosln4bxblwq9.png)
Now, we can also write the above equation as
![4^(5x)=(4)^(2(2x-1))](https://img.qammunity.org/2020/formulas/mathematics/high-school/n549ogvjywu4bc3cxzoq2rb7wd94b9ra6f.png)
![4^(5x)=(4)^((4x-2))](https://img.qammunity.org/2020/formulas/mathematics/high-school/pityy6z7x3gd7vhuzjj6u9jqa02bxzt8gv.png)
Now, taking log on both sides
![log(4^(5x) )=log(4^(4x-2))](https://img.qammunity.org/2020/formulas/mathematics/high-school/xwjczcjlktbvpjts2zdswqbsqrpa6pr1zy.png)
So, the above the equation can be written as
5x=4x-2
Simplifying the equation,
5x-4x=2
x= -2
Hence, the value of x = -2. Which satisfy the given equation in the question.